Compassionate de-escalation of life-sustaining treatments in pediatric oncology: An opportunity for palliative care and intensive care collaboration - Cuviello, Andrea; Pasli, Melisa; Hurley, Caitlin; Bhatia, Shalini; Anghelescu, Doralina L.; Baker, Justin N. (Frontiers in Oncology, 2022)
Context: Approximately 40%-60% of deaths in the pediatric intensive care unit (PICU) are in the context of de-escalation of life-sustaining treatments (LSTs), including compassionate extubation, withdrawal of vasopressors, or other LSTs. Suffering at the end of life (EOL) is often undertreated and underrecognized. Pain and poor quality of life are common concerns amongst parents and providers at a child’s EOL. Integration of palliative care decreases suffering and improves symptom management in many clinical situations; however, few studies have described medical management and symptom burden in children with cancer in the PICU undergoing de-escalation of LSTs. Methods: A retrospective chart review was completed for deceased pediatric oncology patients who experienced compassionate extubation and/or withdrawal of vasopressor support at EOL in the PICU. Demographics, EOL characteristics, and medication use for symptom management were abstracted. Descriptive analyses were applied. Results: Charts of 43 patients treated over a 10-year period were reviewed. Most patients (69.8%) were white males who had undergone hematopoietic stem cell transplantation and experienced compassionate extubation (67.4%) and/or withdrawal of vasopressor support (44.2%). The majority (88.3%) had a physician order for scope of treatment (POST – DNaR) in place an average of 13.9 days before death. Palliative care was consulted for all but 1 patient; however, in 18.6% of cases, consultations occurred on the day of death. During EOL, many patients received medications to treat or prevent respiratory distress, pain, and agitation/anxiety. Most received sedative medications, specifically propofol (14%), dexmedetomidine (12%), or both (44%), with opioids and benzodiazepines. Conclusion: Pediatric oncology patients undergoing de-escalation of LSTs experience symptoms of pain, anxiety, and respiratory distress during EOL. Dexmedetomidine and propofol may help prevent and/or relieve suffering during compassionate de-escalation of LSTs. Further efforts to optimize institutional policies, education, and collaborations between PICU and palliative care teams are needed.